2015
DOI: 10.5551/jat.28829
|View full text |Cite
|
Sign up to set email alerts
|

UFM1 Protects Macrophages from oxLDL-Induced Foam Cell Formation Through a Liver X Receptor α Dependent Pathway

Abstract: Aim: Macrophage foam cell formation is the most prominent characteristic of the early stages of atherosclerosis. Ubiquitin Fold Modifier 1 (UFM1) is a new member of the ubiquitin-like protein family, and its underlying mechanism of action in macrophage foam cell formation is poorly understood. Our current study focuses on UFM1 and investigates its role in macrophage foam cell formation. Methods: Using real-time quantitative PCR (qRT-PCR) and western blot analysis, we first analyzed the UFM1 expression in mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…Previously, both our group (28) and other studies (27,29) indicate that Ufm1 is involved in ER stress, which is a key process of macrophage differentiation and cholesterol deposition in the development of AS (3032). Our follow-up study also showed that Ufm1 is markedly upregulated under AS conditions and Ufm1 suppresses foam cell formation via the LXRα-dependent pathway (33). …”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Previously, both our group (28) and other studies (27,29) indicate that Ufm1 is involved in ER stress, which is a key process of macrophage differentiation and cholesterol deposition in the development of AS (3032). Our follow-up study also showed that Ufm1 is markedly upregulated under AS conditions and Ufm1 suppresses foam cell formation via the LXRα-dependent pathway (33). …”
Section: Introductionmentioning
confidence: 67%
“…It has been reported that Ufm1 is expressed in many tissues and cell lines (19,27) and that upregulation of Ufm1 expression is linked with the activation of the ER stress response in AS and diabetes (27,28,33,35). Our previous studies also demonstrated that Ufm1 is involved in AS conditions (28,33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By searching functions of some newly detected genes, it seems that they have associations with cholesterol. For example, previous experimental analyses showed the gene UFM1 increase the macrophage cholesterol efflux, which might due to the increased expression of ATP-binding cassette transporters A1 ( ABCA1 ) and G1 ( ABCG1 )51; ABCA1 gene was reported to be associate with total cholesterol in previous genome-wide association study (GWAS)5. Previous GWAS reported the 400 kb upstream variant of UMF1 to be associate with plasma lipoprotein levels52.…”
Section: Discussionmentioning
confidence: 99%